The drivers of mental health service utilisation among public primary healthcare workers in Negeri Sembilan - Norhafizah Mohd Noor; Ahmad Azuhairi Ariffin; Halimatus Sakdiah Minhat; Lim Poh Ying; Umi Adzlin Silim (PLoS ONE, 2025)
Background Public primary healthcare workers (HCWs) face various psychosocial risks at workplace that can impact their mental health. However, little is known about their mental health service utilisation (MHSU). This study aimed to determine prevalence and predictors of MHSU among public primary HCWs in Negeri Sembilan, using Anderson Behavioural Model of Health Service Use. Methods A cross-sectional study was conducted from December 2022 to April 2023, using a valid and reliable self-administered six sections questionnaire consisting of; (i) sociodemographic, (ii) work-related factors, (iii) MHSU, (iv) perception of stigmatisation by others, (v) enabling factors, and (vi) need factors. Respondents were selected through proportionate stratified random sampling based on job categories. Multiple Logistic Regression using SPSS version 26 was used to determine the predictors of MHSU. Results A total of 294 respondents participated in this study, with a response rate of 83.5%. The 12-months MHSU prevalence was 45.6%. Mental health services were predominantly utilised for screening (96.3%) and treatment purposes (28.4%), primarily accessed through health clinics (85.1%), and interaction with paramedics (44.0%) and medical officers (38.8%). Significant drivers predicting MHSU were B40 household income (aOR = 3.426, 95% CI: 1.588, 7.393, p-value = 0.002) and M40 household income (aOR = 3.781, 95% CI: 1.916, 7.460, p-value<0.001), low supervisor support (aOR = 2.302, 95% CI: 1.206, 4.392, p-value = 0.011), received mental health training (aOR = 2.058, 95% CI: 1.221, 3.469, p-value = 0.007) and high co-worker support (aOR = 1.701, 95% CI: 1.034, 2.798, p-value = 0.036). Conclusion Almost half of respondents used mental health services, predicted by lower and middle household income, received mental health training and high co-worker support. Conversely, MHSU was also predicted by low supervisor support. To sustain high levels of MHSU, it is essential to implement regular mental health training targeted HCWs with lower to middle household incomes and those experiencing low supervisor support, while simultaneously enhancing co-worker support and screening program for early detection of mental health problems.